Effect of Rice Straw and Sand Residues on Peanut Plants on Several Soil Properties - Narka, I Wayan; Adnyana, I Made (International Journal of Biosciences and Biotechnology, 2025)
The purpose of this study was to determine the effect of rice straw and sand residue on the second crop, namely peanut plants and some soil properties. The design used was a Randomized Block Design in the form of Factorial. The rice straw residue factor consists of 3 levels: RJ0 = without rice straw, RJ1 = 10 tons of rice straw residue ha-1, and RJ2 = 20 tons of rice straw ha-1. The sand addition residue factor consists of 3 levels: RP0 = without sand residue, RP1 = 10% sand residue and RP2 = 20% sand residue. The parameters observed: plant height, dry weight of stover, dry weight of peanut pods, dry weight of peanut seeds and several soil properties such as: soil bulk density, total porosity, nitrogen content, phosphorus, potassium, C-organic content of soil. The results of the study showed that the residue of rice straw provision had a very significant effect on the dry weight of the stover, the dry weight of the pods and the dry weight of the seeds but did not have a significant effect on the height of the plant. The residue of rice straw application of 20 tons ha-1 can increase the dry weight of the seed by 34.01% compared to the control. The residue of sand application and the interaction between the residue of rice straw application and sand did not significantly affect the growth and yield of peanut plants.